Didactic-pedagogical-healthy methodology for the integral attention of cardiopathy pupils from Physical Education (Original) (Revista científica Olimpia, 2022)
In the article it was argued, from theoretical and practical perspectives, the ways to solve the insufficiencies detected in the healthy educational dimension of the teaching-learning process of Physical Education in Primary Education. The study evidenced insufficiencies in the healthy theoretical-methodological conception of this process that limit the integral physical-educational development of pupils, there, a methodology is offered based on a didactic-healthy-pedagogical model, which expresses the dynamics of the systemic relations to achieve the attention of all pupils and which reveals the healthy-pedagogical functionality of the teaching-learning process of Physical Education. The methodology for the treatment of the healthy educational dimension in the reared process is supported by the implementation of didactic procedures in favor of the integral physical-educational development of pupils at this level of education, which guarantees the fulfillment of the proposed objective. The results that show the feasibility and relevance of the implemented methodology are described, based on the transformations achieved in the integrality of Primary Education pupils in the municipality of Las Tunas, hence its relevance and importance.
Keywords: benign breast conditions; fibrocystic breast disease; mammary fibroadenoma; breast cancer.